Cellulose Gels and Microgels: Synthesis, Service, and Supramolecular Interactions - Li, Pingping; Liu, Ruigang (Supramolecular Polymer Networks and Gels, 2015)
This chapter provides an overview of recent research on cellulose-based gels and microgels cross-linked by and/or subject to supramolecular interactions, in which native cellulose, regenerated cellulose, cellulose derivatives, and cellulose graft copolymers are used as the building blocks. Supramolecular interactions such as hydrophobic interactions, hydrogen bonding, and ionic interactions act as a physical means of cross-linking within these cellulose-based gels and microgels. The resulting “smart” supramolecular gels and microgels have many advantages, with a particular view to their intelligent behavior in reaction to environmental stimuli such as pH, temperature, light, electricity, magnetic fields, and mechanical forces, all mediated by specific supramolecular polymer–polymer and polymer–solvent interactions. Cellulose-based supramolecular gels and microgels have been applied or have promising potential for applications in tissue engineering, drug delivery, blood purification, sensors, agriculture, water purification, chromatographic supports, and catalyst supports. This review provides information on using celluloses as building blocks for the fabrication of functional supramolecular materials that are not limited to just gels and microgels.